Um portal inteligente para o debate de teses - Moreli, Jeferson Lopes Dias (2023)
With the advancement of information technology, popularization of computational means, expansion of the internet, the user is no longer just a consumer of content and has also become a major producer. With these changes, new interactions and discourses on distance education have been proposed for the advancement and improvement of their Virtual Teaching and Learning Environments (AVEA). With these adaptations, AVEA began to give greater importance to tools that allow greater interaction between their participants and help them in building their own knowledge. Using these advanced technologies of today's society is an initiative that expands the educational potential of digital technologies and allows teachers to diversify their activities so that they take advantage of the potential of digital technologies. One of the ways is to create virtual environments that provide means of exchanging information, to promote interactions between people, making it possible for them to enrich their knowledge through the debate of ideas, and that favors the teacher to intervene and mediate these debates. The starting point of a Thesis Debate is a set of statements about a theme. It is understood here that Theses are statements that have the potential to generate a relevant volume of imbalances on the subject under study so that participants, based on their prior knowledge, can re-signify them based on interactions. Although the use of the Debate de Theses pedagogical architecture is already a reality, its use is not something trivial. The pedagogical interactions that occur during the application of this architecture are carried out through the production of texts. The pedagogical mediation of these texts demands a considerable amount of time on the part of the teacher. Aiming to reduce this time, in this work we propose a conceptual model, an implementation proposal for a portal for the Debate of Theses Pedagogical Architecture powered by artificial intelligence techniques and we present some alternatives to facilitate the teacher's mediation. We also present a proposal for a continuation of the Debate of Theses Pedagogical Architecture, which can further enhance the development of the participants, as well as considerably reduce the amount of text that the mediator needs to read and interpret to give feedback to the participants after the argumentation stage Final.